Synthesis of 2-Chloro-4-[p-Nitrophenyl Thiourea]-6-[3’-Arylazo-4’-Hydroxy-1’-Napthyl]-s-Triazine Derivatives and Their Application on Cotton and Wood Fibres - Desai, K.R.; Patel, A.H. (Asian Journal of Chemistry, 2010)
Attempts have been made to prepare cyanuric chloride derivatives by condensation of naphthol with cyanuric chloride and then with p-nitrophenylthiourea and then diazotised and coupled with various diazo components. These compounds were evaluated for their dyeing properties on cotton and wool. The structure of these compounds have been confirmed by elemental analysis, IR and NMR spectral studies.